Benzothiazole-decorated iridium-based nanophotosensitizers for photodynamic therapy of cancer cells. Issue 9 (15th February 2022) - Wang, Xiang; Song, Kang; Deng, Yong; Liu, Jie; Peng, Qin; Lao, Xiao; Xu, Jiayu; Wang, Dong; Shi, Turong; Li, Yuhao; Deng, Dan; Miao, Yuqing
Abstract : A folic acid-modified amphiphilic polymer wraps iridium complexes to form three nanophotosensitizers that are applied for cancer cell photodynamic therapy. Abstract : Photodynamic therapy (PDT) is an effective non-invasive treatment for tumors. The structure of a photosensitizer has an important influence on light utilization and efficiency of singlet-oxygen generation. In this study, we synthesized three π-type iridium(iii ) complexes and modified the C^N and N^N ligands with benzothiazole (BTZ) to regulate their light-absorption capacity and efficiency of singlet-oxygen generation. We assembled the nano-photosensitizers by wrapping them with an amphiphilic polyethylene glycol polymer with folic acid-targeting function to improve their targeting ability and biocompatibility. Modification of the BTZ group on the C^N ligand enhanced the ability of the photosensitizer to generate singlet oxygen and improved the cell uptake and PDT efficacy of the corresponding nanophotosensitizer. We believe that this type of photosensitizer provides the basis for the design of new photosensitizers based on the structure of iridium(iii ) complexes.